The ethics of literary communication : genuineness, directness, indirectness - Sell, Roger D.; Borch, Adam; Lindgren, Inna (Dialogue studies, 2013)
Viewing literature as one among other forms of communication, Roger D. Sell and his colleagues evaluate writer-respondent relationships according to the same ethical criterion as applies for dialogue of any other kind. In a nutshell: Are writers and readers respecting each other's human autonomy? If and when the answer here is "Yes!", Sell's team describe the communication that is going on as 'genuine'. In this latest book, they offer new illustrations of what they mean by this, and ask whether genuineness is compatible with communicational directness and communicational indirectness. Is there.